The United States Leather Company and Its Reorganization - Dewing, Arthur S. (Quarterly Journal of Economics, 1911)
Economic disadvantages of combination in the sole leather industry, 69. — Promotion of the United States Leather Co., 70. — Early and continued failure of the company, 72. — Speculative character of its stocks, 73. — Underlying causes of its failure, 75. — First plan of financial readjustment, 77. — Second plan and the reasons for its lapse, 78. — Revaluation of the assets of the company, and third plan, 82. — Motive back of this third plan, 83. — Fourth and final plan of reorganization, 85. — Justice of this plan, 92. — Subsequent litigation and the settlement, 100.